The role of fat mass and obesity associated gene (fto) in satiety and binge eating disorder - Dias de Castro, Mariana Laitano; Horvath, Jaqueline Driemeyer Correia; Kops, Natalia Luiza; Friedman, Rogerio (Clinical and Biomedical Research, 2016)
Obesity is a major health problem and one of the biggest predictors of the development of chronic diseases. Variations in the Fat mass and obesity associated gene (FTO) have been shown to associate strongly with obesity. Among patients with severe obesity, there is a subpopulation that presents an eating disorder known as Binge Eating Disorder. Because of its expression in the hypothalamus, FTO could be associated with modulation of satiety and, perhaps, play a role in the genesis of BED, contributing to severe obesity. A search in PubMed was carried out with the following terms: Morbid Obesity AND FTO, FTO AND Satiety Response, Binge Eating Disorder AND FTO. No restriction on the date of publication, language or type of design was applied. Sixteen articles were found. Twelve were related to FTO and grade III obesity, and three were related to FTO and satiety. Ten studies were excluded. Thus, six articles were evaluated in this review. The scarce literature limits further conclusions about the potential impact of the associations with FTO in the treatment of obesity, but all articles included in this revision show association with at least one SNP of FTO. Further studies are required to clarify these associations, especially in relation to rs9939609 (A/T), because, up to this moment, it seems to be the one variant with greatest impact on obesity in humans.